1988
DOI: 10.1083/jcb.106.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Microfilament modification by dihydrocytochalasin B causes retinoic acid-modulated chondrocytes to reexpress the differentiated collagen phenotype without a change in shape.

Abstract: Abstract. Primary monolayers of rabbit articular chondrocytes synthesize high levels of type II collagen and proteoglycan. This capacity was used as a marker for the expression of the differentiated phenotype. Such cells were treated with 1 Bg/ml retinoic acid (RA) for 10 d to produce a modulated collagen phenotype devoid of type II and consisting of predominantly type I trimer and type III collagen. After transfer to secondary culture in the presence of RA, the stability of the RA-modulated phenotype was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
94
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(105 citation statements)
references
References 54 publications
(87 reference statements)
9
94
2
Order By: Relevance
“…Indeed, the microfilament-disruptive drug, cytochalasin, induces reexpression of chondrocyte phenotype in monolayers of both subcultured and retinoic acid-modulated chondrocytes (38,39). Although microfilament modification is an important mediator of the chondrocyte phenotype, ERK regulation of chondrocyte dedifferentiation is not mediated by the modification of actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the microfilament-disruptive drug, cytochalasin, induces reexpression of chondrocyte phenotype in monolayers of both subcultured and retinoic acid-modulated chondrocytes (38,39). Although microfilament modification is an important mediator of the chondrocyte phenotype, ERK regulation of chondrocyte dedifferentiation is not mediated by the modification of actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Forcing spherical cell shape by pharmacological inhibition of actin polymerization is sufficient to stimulate dedifferentiated cells to re-express chondrogenic matrix molecules (21)(22)(23)(24) and promotes mesenchymal cells to commit to the chondrogenic lineage (24,25). We therefore speculated that signaling pathways that regulate cell shape also regulate chondrocyte differentiation.…”
mentioning
confidence: 99%
“…However, recent in situ hybridization studies of cultured chick embryo chondrocytes indicated a lack of correlation between changes in cell shape and expression of cartilage-specific genes (20). Other investigators have related the modulation of cartilage-specific gene expression in cultured chondrocytes to the degree of polymerization of the actin cytoskeletal elements (21,22).…”
mentioning
confidence: 99%